Magnesium battery cycling stability enhancing material and application thereof
The V2O5 nanomaterial prepared by the solvent thermal method solves the problem of stacking and agglomeration of V2O5 nanosheets in the traditional preparation process, realizes the efficient preparation of the positive electrode material of magnesium battery, and improves the cycle stability and storage capacity of the battery.
Patent Information
- Application Number
- CN202411935218.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-26
AI Technical Summary
V2O5 positive electrode material has disadvantages such as poor conductivity and unstable structure in magnesium batteries, resulting in limited application in metal ion batteries.
The obtained V2O5 nanomaterial prepared by solvothermal method is used as the positive electrode material of magnesium battery, with a super-porous structure and ion transport channel, and the three-dimensional size is only about 5um, which solves the problem of stacking and agglomeration of V2O5 nanosheets in traditional preparation technology.
It effectively improves the surfactant state, exposes more active sites, provides multiple and short channel paths for the rapid transfer of electrons, realizes effective deintercalation of ions, and improves the cycling stability and storage capacity of the battery.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy storage technology, and specifically relates to a magnesium battery cycle stability enhancing material (specifically coral-like V2O5-based magnesium battery positive electrode material), a preparation method and application thereof in a magnesium battery. Background Art
[0002] In recent years, with the continuous exploration and development of clean energy and renewable energy (solar energy, wind energy, tidal energy, etc.), efficient energy storage systems have attracted the attention of scientific researchers. V2O5 is widely used in various types of batteries, such as lithium-ion batteries, lead-acid batteries, etc. due to its excellent performance. As a positive electrode material in the battery, V2O5 has high specific capacity and excellent cycle performance, and has broad application prospects in improving battery performance and life. As a transition metal oxide, V2O5 has abundant reserves, low cost and good safety. Compared with other electrode materials, V2O5 has a specific capacity of up to 300mAh / g, which is several times that of many materials. In addition, when the cycle test is carried out at room temperature, the capacity retention rate of V2O5 is as high as 85%.
[0003] In recent years, V2O5 has been widely used in a variety of new battery fields, especially zinc-ion batteries, and has demonstrated excellent ion storage capacity, extraordinary capacity and rate performance. Due to the diversity of V2O5 preparation, various forms of V2O5 have been developed, such as sea urchin-shaped, windmill-shaped, fiber-spinning-shaped, etc. These forms optimize the electrochemical performance of the battery to a certain extent, and even promote the redox reaction through exposed active sites.
[0004] However, relatively speaking, the low ion diffusion coefficient, low conductivity and structural instability caused by repeated ion insertion / deinsertion of V2O5 positive electrode materials have limited their application in metal ion batteries. In order to solve these problems, researchers have carried out a series of studies through modification methods such as morphology control, crystal structure modification, chemical pre-insertion and composite with other materials. For example, Chinese invention patent CN118825249A discloses an amorphous carbon-coated three-dimensional porous cellular VO2 / V2O5 composite material, which provides multiple active sites while the outer layer is coated with carbon. The three-dimensional conductive network formed by cross-linking between them effectively improves the ionic conductivity and electronic conductivity of the electrode system. CN118598186A publicly released a V2O5 / H x V2O5 composite cathode material, expanding Zn by proton insertion 2+ The diffusion path of Zn 2+ The interaction with the V2O5 lattice improves the rate performance of aqueous zinc-ion batteries.
[0005] Among all the research methods, improving the morphology of V2O5 is the simplest and most convenient way to improve the electrochemical performance of batteries. Through microscopic regulation of the morphology during the preparation process, its ability to absorb metal ions is enhanced. Currently, researchers have improved the morphology through electrospinning, chemical vapor deposition technology, hydrothermal and other methods, but V2O5 still has shortcomings such as poor conductivity and unstable structure, and sometimes even serious accumulation occurs, leading to structural collapse.
[0006] Therefore, developing a structurally stable, economical and efficient preparation method remains a key project for future research. Based on this, this application was developed. Summary of the invention
[0007] In view of the problems existing in the traditional preparation method, the present invention proposes a preparation method of a material for enhancing the cycle stability of a magnesium battery. The method uses a V2O5 nanomaterial prepared by a solvothermal method as a positive electrode material for a magnesium battery, which has an ultra-porous structure and an ion transmission channel, and a three-dimensional size of only about 5um, which solves the problem of stacking and agglomeration of V2O5 nanosheets in the traditional preparation process, effectively improves the surface active state, exposes more active sites, and provides multiple and short channel paths for the rapid transfer of electrons, and exhibits excellent cycle stability.
[0008] The present invention also provides the above-mentioned magnesium battery cycle stability enhancing material and application thereof in magnesium batteries.
[0009] Based on the above purpose, the present invention adopts the following technical solutions: A method for preparing a magnesium battery cycle stability enhancing material comprises the following steps: 1) Take an appropriate amount of vanadium source and surfactant and dissolve them in a mixed solution of isopropanol and diethylene glycol to obtain a colored solution A; 2) Place solution A in a hydrothermal reactor and perform hydrothermal reaction at 180-200 °C for 18-24 h; the filling ratio in the hydrothermal reactor is 60-70%; 3) After the hydrothermal reaction, the precursor powder material is obtained by washing and drying; 4) The precursor powder material is heated to 400-500°C and kept warm for 1-5 hours, and then cooled to obtain a coral-like V2O5-based magnesium battery positive electrode material with a specific (110) crystal plane exposed, with a diameter of 2-10 μm, a thickness of 5-10 nm, and a width of 30-100 nm.
[0010] Specifically, the vanadium source in step 1) is NH4VO3 and / or commercial V2O5 powder. The surfactant in step 1) is one or more of citric acid monohydrate (C6H8O7·H2O), polyvinylpyrrolidone (PVP), hexadecyltrimethylammonium bromide (CTAB), etc.
[0011] Furthermore, in step 1), the mass ratio of the vanadium source to the surfactant is 1:2-4.
[0012] Furthermore, the volume ratio of isopropanol to diethylene glycol in 1) is 1:0.5~2. In step 1), a 100±15°C water bath can be used for heating and magnetic stirring until the mixture is completely dissolved, and the magnetic stirring time is 1~1.5 h.
[0013] Furthermore, the hydrothermal temperature in step 2) is 180-200 °C. Repeated experiments have shown that under this condition, the purity of V2O5 is the highest, the yield is the largest, the structure is the most stable, and the morphology is also good, which is the optimal process condition.
[0014] Specifically, in step 3), the precipitate is washed with ethanol for 3 to 5 times, and then freeze-dried by freeze-drying technology, frozen in a refrigerator for 8 to 12 hours, and then freeze-dried at -55±10°C for 10 to 24 hours.
[0015] Furthermore, in step 4), the temperature is raised to the heating temperature in the muffle furnace at a heating rate of 5-10 °C / min.
[0016] The present invention provides a magnesium battery cycle stability enhancing material (coral-shaped V2O5-based magnesium battery positive electrode material) prepared by the above method.
[0017] The present invention also provides the use of the above-mentioned magnesium battery cycle stability enhancing material (coral-like V2O5-based magnesium battery positive electrode material) in a magnesium battery.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts a solvothermal method to prepare V2O5 nanomaterials as the positive electrode material of magnesium batteries. The nanomaterials have ultra-porous structures and ion transmission channels, and the three-dimensional size is only about 5um. The problem of stacking and agglomeration of V2O5 nanosheets in the traditional preparation process is solved, the surface active state is effectively improved, more active sites are exposed, and multiple and short channel paths are provided for the rapid transfer of electrons, while achieving effective ion deintercalation. In addition, the exposed (110) crystal plane can also reduce the interface side reactions between the electrode and the electrolyte surface, so that the yield of the surface passivation film is greatly reduced, thereby greatly improving its storage capacity and showing excellent cycle stability. In addition, the preparation process of the present invention is short, the production efficiency is high, the output is high, the production volume is large, the product purity is good, the preparation time is fast, the cost is low, and it has good repeatability, and it can avoid the problem of stacking and agglomeration of traditional sheet V2O5.
[0019] The present invention uses coral-like V2O5 nanomaterials as the positive electrode material for magnesium batteries. Its open three-dimensional porous structure not only increases the attachment sites of ions, but also provides a multi-channel path for the transfer of electrons. In addition, the exposed (110) crystal plane reduces the interface side reactions between the electrode and the electrolyte surface, reduces the generation of passivation film on the electrode surface, thereby accelerating the redox reaction of the battery, has very high capacity storage and good rate performance, and is an excellent positive electrode material for magnesium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 are SEM images of the coral-like V2O5 nanomaterials prepared in Examples 1 (a), 2 (b), 3 (c), and 4 (d) of the present invention; Figure 2 is a cross-sectional SEM image of the coral-like V2O5 prepared in Example 1 of the present invention exposed in a broken state; Figure 3 are optical electron microscope images of precursors of different colors before calcination in Examples 1 (a), 2 (b), 3 (c), and 4 (d) of the present invention; Figure 4 is the X-ray diffraction pattern of the coral-like V2O5 nanomaterial obtained after calcination in Examples 1-4 of the present invention; Figure 5 Coral-like V2O5 nanomaterials prepared in Examples 1-4 of the present invention 50 mA g −1 The first 100 cycles of the current density are shown in the graph; Figure 6 This is a rate performance diagram at different current densities after 20 cycles of activation of Example 1 of the present invention. DETAILED DESCRIPTION
[0021] The following are specific embodiments of the present invention, and the technical solution of the present invention is further described in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited thereto.
[0022] In the following examples, the raw materials used are all common commercial products that can be directly purchased or can be prepared using conventional techniques in the art. Room temperature refers to 25±5°C.
[0023] Example 1 1) Dissolve 0.4 g of NH4VO3 and 1.2 g of CTAB in 60 mL of a mixed solution of isopropanol and diethylene glycol (the volume ratio of isopropanol and diethylene glycol is 1:1), heat to 100°C in a water bath, and stir magnetically for 1 h until completely dissolved to obtain a gray-blue solution; 2) Place the solution in a hydrothermal reactor at a hydrothermal temperature of 200 °C for 24 h with a filling ratio of 60%; 3) After the reaction, centrifuge and wash the precipitate obtained by the reaction with ethanol three times, then freeze it in a refrigerator for 12 hours, and freeze-dry it in a freezer at −55 °C and a vacuum degree of 1 Pa for 24 hours to obtain a dark purple precursor powder material; 4) Heat the precursor material in a muffle furnace at 5 °C min −1 The mixture was heated to 400 °C at a heating rate of 1.5 ℃, kept in air for 2 h, and then cooled to room temperature with the furnace to obtain orange-yellow coral-like V2O5 with an average diameter of 5 μm.
[0024] Example 2 1) Dissolve 0.4 g of NH4VO3 and 1.2 g of PVP in 60 mL of a mixed solution of isopropanol and diethylene glycol (the volume ratio of isopropanol and diethylene glycol is 1:1), heat to 100 °C in a water bath, and stir magnetically for 1 h until completely dissolved to obtain a gray-brown solution; 2) Place the solution in a hydrothermal reactor at a hydrothermal temperature of 200 °C for 24 h with a filling ratio of 60%; 3) After the reaction, centrifuge and wash the precipitate obtained by the reaction with ethanol three times, then freeze it in a refrigerator for 12 hours, and freeze-dry it in a freezer at −55 °C and a vacuum degree of 1 Pa for 24 hours to obtain a light purple precursor powder material; 4) Heat the precursor material in a muffle furnace at 5 °C min −1 The mixture was heated to 400 °C at a heating rate of 1.5 ℃, kept in air for 2 h, and then cooled to room temperature with the furnace to obtain orange-yellow coral-like V2O5 with an average diameter of 5 μm.
[0025] Example 3 1) Dissolve 0.4 g of commercial V2O5 powder and 1.2 g of C6H8O7·H2O in 60 mL of a mixed solution of isopropanol and diethylene glycol (the volume ratio of isopropanol to diethylene glycol is 1:1), heat to 100 °C in a water bath, and stir magnetically for 1 h until completely dissolved to obtain a dark blue solution; 2) Place the solution in a hydrothermal reactor at a hydrothermal temperature of 200 °C for 24 h with a filling ratio of 60%; 3) After the reaction, centrifuge and wash the precipitate obtained by the reaction with ethanol three times, then freeze it in a refrigerator for 12 hours, and freeze-dry it in a freezer at −55 °C and a vacuum degree of 1 Pa for 24 hours to obtain a dark gray precursor powder material; 4) Heat the precursor material in a muffle furnace at 5 °C min −1 The mixture was heated to 400 °C at a heating rate of , kept in air for 2 h and then cooled to room temperature with the furnace to obtain orange-yellow coral-like V2O5 with an average diameter of 4 μm.
[0026] Example 4 1) Dissolve 0.4 g of NH4VO3 and 1.2 g of C6H8O7·H2O in 60 mL of a mixed solution of isopropanol and diethylene glycol (the volume ratio of isopropanol to diethylene glycol is 1:1), heat to 100 °C in a water bath, and stir magnetically for 1 h until completely dissolved to obtain an orange-yellow solution; 2) Place the solution in a hydrothermal reactor at a hydrothermal temperature of 200 °C for 24 h with a filling ratio of 60%; 3) After the reaction, centrifuge and wash the precipitate obtained by the reaction with ethanol three times, then freeze it in a refrigerator for 12 hours, and freeze-dry it in a freezer at −55 °C and a vacuum degree of 1 Pa for 24 hours to obtain a light purple precursor powder material; 4) Heat the precursor material in a muffle furnace at 5 °C min −1 The mixture was heated to 400 °C at a heating rate of 1.5 ℃, kept in air for 2 h, and then cooled to room temperature with the furnace to obtain orange-yellow coral-like V2O5 with an average diameter of 5 μm.
[0027] Figure 1 The scanning pattern comparison diagram of Examples 1-4 of the present invention is shown. It can be seen from the figure that the average yield of the V2O5 nanomaterial obtained in Example 1 is 483 mg, and the average diameter is 5 μm; the average yield of the coral-like V2O5 nanomaterial obtained in Example 2 is 285 mg, and the average diameter is 5 μm; the average yield of the coral-like V2O5 nanomaterial obtained in Example 3 is 278 mg, and the average diameter is 4 μm; the average yield of the coral-like V2O5 nanomaterial obtained in Example 4 is 250 mg, and the average diameter is 5 μm. The stable coral-like V2O5 structure effectively improves the surface active state, exposes more active sites, and provides multiple and short channel paths for the rapid transfer of electrons, realizing the effective deintercalation of ions.
[0028] Figure 2 The scanned image of the broken cross section of coral-like V2O5 in Example 1 is shown. It can be seen from the figure that it is composed of many branches with uniform morphology, which are dispersed from the center to the outside, and there is a small hollow sphere in the center. This structure is easier to accommodate ions and realize rapid charge transmission.
[0029] Figure 3 The optical electron microscope images of the precursor powders of Examples 1 to 4 before calcination are shown. The results show that Example 1 is dark purple, Example 2 is light purple, Example 3 is dark gray, and Example 4 is the lightest in color, but also purple.
[0030] Figure 4The XRD diagrams of Examples 1-4 after calcination, among which Example 1 has the highest peak intensity and the best crystallinity, and at the same time exposes a specific (110) crystal plane. The crystal plane exposed in Example 2 is the (001) crystal plane, and the crystallinity is slightly weaker. The (110) crystal planes of Examples 3 and 4 are also the strongest, but the crystallinity of Example 4 is a little weaker. Exposing more (110) crystal planes means that there are more active sites, the amount of passivation film generated is the least, and the interface side reaction between the electrode and the electrolyte surface is minimal, which is beneficial to the electrochemical performance of the battery.
[0031] In order to verify that the above method can obtain coral-like V2O5 nanomaterials with excellent performance, the coral-like V2O5 nanomaterial sample obtained in Example 1 was prepared as the positive electrode material of a magnesium battery, and magnesium foil was used as the negative electrode of the battery. They were assembled into 2032-type button batteries, and their electrochemical properties were tested in the voltage range of 0.1 ~1.9 V.
[0032] The production process of the battery pole piece is as follows: the above coral-like V2O5 nanomaterial, conductive carbon black and adhesive PVDF are uniformly mixed in a mass ratio of 7:2:1, and an organic solvent N-methylpyrrolidone is added to obtain a positive electrode slurry. The positive electrode slurry is coated on a copper foil, and the coating thickness is controlled to be 50 um. After drying, rolling and punching, a magnesium battery positive electrode sheet is obtained.
[0033] The preparation process of the electrolyte is as follows: first, add 6 ml of anhydrous tetrahydrofuran (THF ≥ 99.9%) to beaker 1, weigh 0.534 g of anhydrous AlCl3, add it and stir continuously; add 4 ml of 2 mol / L phenylmagnesium chloride solution to beaker 2, then use a dropper to add the liquid in beaker 2 dropwise to beaker 1, continue stirring for 16 hours, and obtain APC solution. Weigh 0.4239 g of LiCl and measure 5 ml of THF in a beaker, stir until completely dissolved, add 5 ml of the prepared APC solution dropwise, mix and stir for 12 hours to obtain a mixed electrolyte.
[0034] Figure 5 The results are shown for Examples 1-4 at 50 mA g −1 The charge and discharge cycle curve under current density. The results show that after 100 cycles, the capacity of Example 1 remains at 102.4 mAh g −1 , the capacity retention rate is the highest.
[0035] Figure 6 The rate performance diagram of Example 1 and commercial V2O5 at different current densities after 20 cycles of activation. The results show that at 500 mA g −1 At high current density, Example 1 can still maintain 78.9 mAh g −1The capacity is much higher than that of commercial V2O5, demonstrating its good rate performance.
[0036] In summary, compared with the prior art, the preparation method of the present invention is efficient and fast. The prepared V2O5 product has a super porous structure and ion transmission channels, which solves the problem of stacking and agglomeration of V2O5 nanosheets in the traditional preparation process, effectively improves the surface active state, exposes more active sites, and provides multiple and short channel paths for the rapid transfer of electrons, while achieving effective ion deintercalation. In addition, the exposed (110) crystal plane can also reduce the interface side reactions between the electrode and the electrolyte surface, greatly reducing the yield of the surface passivation film. As a positive electrode material for magnesium batteries, its storage capacity is greatly improved and it exhibits excellent cycle stability.
Claims
1. A method for preparing a magnesium battery cycle stability enhancing material, characterized in that: The steps include: 1) dissolving an appropriate amount of vanadium source and surfactant in a mixed solution of isopropanol and diethylene glycol to obtain solution A; 2) Hydrothermally react solution A at 180-200 °C for 18-24 h; 3) After the hydrothermal reaction, the precursor powder material is obtained by washing and drying; 4) Heat the precursor powder material to 400~500℃ and keep it warm for 1~5h, then cool it.
2. The preparation method according to claim 1, characterized in that: The vanadium source in step 1) is NH4VO3 and / or commercial V2O5 powder.
3. The preparation method according to claim 1, characterized in that: The surfactant in step 1) is one or more of citric acid monohydrate, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the vanadium source to the surfactant in step 1) is 1:2-4.
5. The preparation method according to claim 1, characterized in that: In step 1), the volume ratio of isopropyl alcohol to diethylene glycol is 1:0.5-2.
6. The preparation method according to claim 1, characterized in that: In step 1), heat in a 100±15°C water bath and stir magnetically until the solution is completely dissolved. The magnetic stirring time is 1 to 1.5 h.
7. The preparation method according to claim 1, characterized in that: In step 3), wash with ethanol 3 to 5 times, then freeze the precipitate in a refrigerator for 8 to 12 h, and then freeze-dry at −55 ± 10 °C for 10 to 24 h.
8. The preparation method according to claim 1, characterized in that: In step 4), the temperature is raised to the heating temperature in a muffle furnace at a heating rate of 5-10 °C / min.
9. A magnesium battery cycle stability enhancing material prepared by the method according to any one of claims 1 to 8.
10. Use of the magnesium battery cycle stability enhancing material according to claim 9 in a magnesium battery.
Citation Information
Patent Citations
Preparation method and application of V2O5 / HxV2O5 composite positive electrode material
CN118598186A
Amorphous carbon coated porous cellular VO2 / V2O5 composite material as well as preparation method and application thereof
CN118825249A
Preparation method of self-assembled lithium ion battery positive material V2O5
CN104993116A
Preparation and application methods of nanometer carbon sphere-supported MXene composite material
CN109449402A
Preparation method of lithium vanadate nanomaterial with coral morphology
CN110759381A